Anti-Candidal Efficacy of Alternative Natural Formulations as a Denture Cleansing Agent – Is Ayurveda the Answer? – An In-vitro Study - Kritika Rajan; Rahul Paul; Ishan R. Choudhury; Dhina Pal; Richa Bansal; Abhishek Shekhar; Mradu Gupta (Journal of Pharmacy and Bioallied Sciences)
The purpose of this study was to evaluate the anti-candidal effectiveness of several household products, such as ayurvedic medicines, to established denture cleaning agents. Acrylic samples were compared to denture cleaning pills and chlorhexidine after being submerged in a variety of freshly made ayurvedic formulations, vinegar, and home bleach for 20 minutes, and the total Candida counts (CFU/4 cm2) were measured. It was discovered that vinegar (87.36%) and Clinsodent tablets (94.66%) were the most effective against Candida albicans. The aqueous extract of triphala (34.50%) was more effective than the hydroalcoholic extract (18.86%), according to the ayurvedic product’s data. Commercial denture cleaner was shown to have the strongest anti-candidal efficacy. In terms of anti-candidal potency, the inexpensive Triphala churna, which has been used in rural India, is not far behind.